Penerapan Terapi Kognitif dan Family Psychoeducation pada Keluarga Disharmoni dengan Risiko Bunuh Diri : Studi Kasus : Penerapan Terapi Kognitif dan Family Psychoeducation pada Keluarga Disharmoni dengan Risiko Bunuh Diri : Studi Kasus - Reza Fajar Amalia; Amalia, Reza Fajar; As'hab, Priyo Purnomo (Jurnal Kesehatan Masa Depan, 2023)
Background: Family conflict is a major precipitating factor of interpersonal stress and is related to ineffective communication patterns within the family. This unresolved stress can have an impact on depression and suicidal behaviour. Managing clients at risk of suicide requires involvement from various aspects, especially the family as the main support system for clients. Purpose: Provide an overview of the application of cognitive therapy and family psychoeducational therapy in disharmony families with suicide risk. Methods: This study was conducted using a case study approach. Case Overview: Mrs I (36 years old) has domestic problems in the form of threats of separation (divorce). The client said that her 40-year-old husband had an affair and wanted to divorce her. The client has two sons, ages 18 and 7. Clients feel anxious, sad, and angry if their household must end in divorce. The client says he can't afford to be a single parent, the client looks hopeless and says he wants to give up on the problem at hand, the client often cries, daydreams, and expresses his wish to die. The client also advised his mother to care for her children after she died. Physical complaints experienced were high blood pressure (> 150/100 mmHg), headaches, palpitations, loss of appetite, and sleep disturbances. Results: A decreased score of suicidal ideation from 78% to 22% and increased family knowledge and ability to care for family members. Conclusion: The application of cognitive therapy and family psychoeducation in cases of non-psychotic suicide risk, especially in disharmony families, has an impact on reducing suicidal ideation and increasing the knowledge and ability of families to care for clients at risk of suicide.